An Assessment of Marketisation of ‘Review’ Through Literature (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
This exploratory qualitative study based on multiple-case studies collects reviewers’ comments using a ‘vector manuscript’ that carries 5 obvious mistakes for assessment. On the basis of the synthesized guidelines prescribed for the reviewers, these comments are measured and assessed. The assessment of the collected review comments of conferences, international journals, and that of the institutional level (N=126), suggests that the elements of negligence and marketisation have already infused in the academics of review. Those who were more oriented towards money were found to be 6.9 times more threatening in comparison to those who were not money-oriented. In this study, at the institutional level, those accepting gifts from the student before reviewing the paper are coded as asking for money.